Simultaneous measurements of LII/LIF/LIS on single-coal-particle combustion - Sawada, Shinya; Okada, Daisuke; Tainaka, Kazuki; Nakatsuka, Noriaki; Hori, Tsukasa; Hayashi, Jun; Akamatsu, Fumiteru (Applied physics. B, Lasers and optics, 2023)
Simultaneous imaging of polycyclic aromatic hydrocarbons (PAHs), soot, and the flame zone formed around a single coal particle was conducted to investigate the flame structure of a single coal particle. The spatial distribution of PAHs, soot, and the flame zone was illuminated using PAHs and CH 2 O laser-induced fluorescence (LIF) and laser-induced incandescence (LII), respectively. Additionally, the spatial distribution of the primary soot particle size was evaluated using a combination of LII and laser-induced scattering (LIS). The results showed that the CH 2 O-LIF imaging was successful for the volatile flame of a single pulverized coal particle. The PAHs-LIF signal was found inside the region where the LII signal was measured, while the CH 2 O-LIF signal was detected outside of the LII signal. The size of soot particles increased, and the soot number density decreased from the interior to the exterior of the volatile flame. Furthermore, the structure of the volatile flame of a single coal particle was found to be identical to that of a diffusion flame.